Are genital examinations necessary for STI screening for female sex workers? An audit of decriminalized and regulated sex workers in Melbourne, Australia. - Evelyn M Turek; Christopher K Fairley; Catriona S Bradshaw; Marcus Y Chen; Lenka A Vodstrcil; Anthony Snow; Ria Fortune; Eric P F Chow (PLoS ONE, 2020)
BACKGROUND:The Victorian legislation prohibits sex workers from working when they have visible anogenital herpes or warts. The aim of this study was to determine the proportion of asymptomatic female sex workers (FSW) diagnosed with anogenital herpes or warts by genital examination. METHODS:We analysed all computerised medical records of consultations with FSW at the Melbourne Sexual Health Centre (MSHC) in 2018. All asymptomatic sex workers were offered screening sexually transmitted infections (STIs) and a genital examination to identify visible anogenital herpes or warts at MSHC. FSW consultations were categorised into either 'asymptomatic' or 'symptomatic' based on the presence of symptoms reported by the FSW to the triage nurse. The proportion of asymptomatic FSW diagnosed with visible anogenital herpes or warts during a routine screening examination was calculated. RESULTS:In 2018, 4055 consultations were provided to 1979 FSW. 3406 of these consultations were asymptomatic and all were examined by an experienced clinician for signs of STIs. Of these 3406 asymptomatic consultations, seven FSW (0.21%, 95% CI: 0.08% to 0.42%) were diagnosed with visible anogenital herpes and/or warts following a genital examination. Four were diagnosed with warts (0.12%, 95% CI: 0.03% to 0.30%), two with herpes (0.06%, 95% CI: 0.01% to 0.21%) and one with both herpes and warts (0.03%, 95% CI: 0.001% to 0.16%). CONCLUSION:Based on these data, approximately 500 asymptomatic FSW would need to be examined to identify one case of anogenital herpes or warts. Genital examinations consume considerable clinical resources, increase the duration of consultations and provide essentially no significant benefit to the mandated testing for gonorrhoea, chlamydia, HIV and syphilis. Our clinic will use self-collected samples and no longer examine FSW who are asymptomatic.